![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 1 : ( 5x - 17 )3 = 27
( 5x - 17 )3 = 33
=> 5x - 17 = 3
5x = 3 + 17
5x = 20
x = 20 : 5
x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(\frac{17}{6}-\left(x-\frac{7}{6}\right)=\frac{7}{4}\)
\(\Rightarrow x-\frac{7}{6}=\frac{17}{6}-\frac{7}{4}\)
\(\Rightarrow x=\frac{13}{12}+\frac{7}{6}=\frac{9}{4}\)
2) \(\frac{3}{35}-\left(\frac{3}{5}-x\right)=\frac{2}{7}\)
\(\Rightarrow\)\(\frac{3}{5}-x=\frac{3}{35}-\frac{2}{7}=-\frac{1}{5}\)
\(\Rightarrow x=\frac{3}{5}-\left(-\frac{1}{5}\right)=\frac{4}{5}\)
3) 4) Hjhj^_^^_^
![](https://rs.olm.vn/images/avt/0.png?1311)
a. -3/4 x 12/-5 x (-25/6)=-15/2
b. -2 x -38/21 x -7/4 x (-3/8)=-19/8
c. (11/12: 33/16) x 3/5=4/15
d. 7/23 x [(-8/6)- 45/18]=-7/6
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(-\frac{6}{7}< \frac{3}{7}< \frac{18}{7}\)
b) \(\frac{17}{35}>\frac{17}{53}\)
c) \(\frac{17}{35}< \frac{17}{-35}\)
d) Ta có : \(\frac{12}{7}=\frac{60}{35}\)
\(\frac{17}{5}=\frac{85}{35}\)
\(\Rightarrow\frac{12}{7}< \frac{17}{5}\)
a)\(\frac{3}{7}\)>\(\frac{18}{7}\)>\(\frac{-6}{7}\)
b)\(\frac{17}{35}\)>\(\frac{17}{53}\)
c)\(\frac{17}{35}\)<\(\frac{17}{-35}\)
d)\(\frac{12}{7}\)<\(\frac{17}{5}\)
hok tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(-\frac{6}{7}< \frac{3}{7}< \frac{18}{7}\)
b ) \(\frac{17}{35}>\frac{17}{-35}\)
c ) \(\frac{17}{35}>\frac{17}{53}\)
d ) \(\frac{12}{7}< \frac{17}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1,
\(\frac{25}{12}+\left(\frac{-4}{12}\right)=\frac{7}{4}\)
\(\frac{-10}{8}+\frac{15}{4}=\frac{5}{2}\)
\(\frac{3}{8}+\frac{-14}{6}=\frac{-47}{24}\)
\(\frac{350}{150}+\left(\frac{-200}{360}\right)=\frac{16}{9}\)
\([\frac{5}{8}+\left(\frac{-3}{4}\right)]+\frac{15}{6}=\frac{-1}{8}+\frac{15}{6}=\frac{19}{8}\)
\(\frac{7}{3}+[\left(\frac{-5}{6}\right)+\left(\frac{-2}{3}\right)]=\frac{7}{3}+\left(\frac{-3}{2}\right)=\frac{5}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x}{6}+\frac{7}{3.2^2}=\frac{17}{18}-\frac{1}{3^2}\)
\(\frac{x}{6}+\frac{7}{12}=\frac{5}{6}\)
\(\frac{x}{6}=\frac{5}{6}-\frac{7}{12}\)
\(\frac{x}{6}=\frac{1}{4}\)
\(x=\frac{1}{4}.6\)
\(x=\frac{3}{2}\)
`17/18+(x-7)/6=(x+12)/3`
`=>17+3(x-7)=6(x+12)`
`=>17+3x-21=6x+72`
`=>3x-4=6x+72`
`=>3x=-76`
`=>x=-76/3`
Vậy `x=-76/3`